A salvação dos ricos no exemplo de Zaqueu - Lorandi, Jaime (2023)
This dissertation addresses the theme of christian salvation and the pedagogy of Jesus described by Luke, aiming to help in the journey and transformation of the rich in modern times and in the increase of help to the poor, as concrete expression of a conversion of conduct through the practice of charity and justice. This work makes a brief study on the sources, recipientes, literary genre and Lucas’ midrash. It issues a hermeneutical analysis of the Luke pericope 19,1-10. It analyzes the moral conduct of the rich publican Zacchaeus, and defends the interpretation of his declared positive honesty before Jesus, who granted him the grace of salvation. It also addresses the possibility that Zacchaeus was baptized and a disciple of John the Baptist, studying historical and biblical elements about the political, social and religious situation of publicans and rich people in the time of Jesus, contextualizing Zacchaeus and his profession in the judaic society of the Pax Romana times. Also makes a biblical reflection on riches and discuss about the evangelization of the entrepeneur. In the end, it concludes that as the salvation of Jesus is for everyone, a specific evangelization is necessary for the vocation of the current business community based on the Christian Social Doctrine and on the example of Zacchaeus's charity and justice.